Interacting fermions in narrow-gap semiconductors with band inversion. (28th May 2021) - Panday, Suman Raj; Dzero, Maxim
Abstract: Highly unconventional behavior of the thermodynamic response functions has been experimentally observed in a narrow gap semiconductor samarium hexaboride. Motivated by these observations, we use renormalization group technique to investigate many-body instabilities in the f -orbital narrow gap semiconductors with band inversion in the limit of weak coupling. By projecting out the double occupancy of the f -states we formulate a low-energy theory describing the interacting particles in two hybridized electron- and hole-like bands. The interactions are assumed to be weak and short-ranged. We take into account the difference between the effective masses of the quasiparticles in each band. Upon carrying out the renormalization group analysis we find that there is only one stable fixed point corresponding to the excitonic instability with time-reversal symmetry breaking for small enough mismatch between the effective masses.